Physicochemical and Structural Properties of Green Biofilms from Poly (Vinyl alcohol)/Nano Coconut Shell Filler. Issue 12 (2nd December 2021) - Balavairavan, B.; Saravanakumar, S.S.; Manikandan, K.M.
ABSTRACT: There is growing interest in recent times to develop biodegradable films with improved properties. They are potential substitutes for existing petroleum-based synthetic polymers. Eco-friendly biofilms based on Poly (vinyl alcohol)/Nano coconut shell filler (PVA/NCSF) were primed by a solution casting method. The biofilms were characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis, Tensile test, FESEM, Transparency Water absorption, biodegradability test, and tensile testing. FTIR and XRD results revealed the structural characterization and crystallinity index of prepared PVA/NCSP biofilms. FTIR suggested that strong hydrogen bonding due to interfacial exchanges of PVA/NCSF. Thermogravimetric analyses revealed thermal degradation temperatures of biofilms that were observed between 259.79°C and 350°C. The tensile strength and elastic modulus were enhanced by 25.5% and 97.25%, respectively, when NCSF was added at 25 wt% level. It is intriguing that % of elongation linearly decreased with the incorporation of filler. The FESEM results evident that good compatibility between PVA and NCSF. The water absorption of PVA/NCSF biofilms slightly increases with increase in the NCSF content. Soil burial test results evident that 34% weight loss of biofilms (25 wt% of NCSF) due to NCSF loading in PVA Matrix. Taken together, the present study confirmed that PVA/NCSF biofilms can be a potential for packaging applications.